Analisis Pengaruh Religiosity,Consumer Ethnocentrism Dan Country Of Originterhadap Purchase Intention (Studi Empiris Dalam Membeli iPhone Oleh Mahasiswa FEB di Universitas Muhammadiyah Surakarta) - Hidayat, Saiful, Soepatini, SE., M.Si., Ph.D (2017)
This study aim to analyze the effect of religiosity, consumer ethnocentrism and country of origin on purchase intention. The independent variables consist of religiosity, consumer ethnocentrism and country of origin, meanwhile the dependent variable is purchase intention. The population of this research is the collage students of economic and business faculty of Muhammadiyah University of Surakarta. The technique of the sample collection was quota sampling and convenience sampling method. The samples are taken from 100 collage students, while the research instrument is in the form of questionnaire. The analysis used in this research includes validity test, reliability test, the classical assumption test, multiple liniear regression analysis, t test, F test and the coefficient of determination analysis (R^2). The result of this research show that religiosity has an significant and negative effect on purchase intention. Consumer Ethnocentrism significantly and negatively influences on purchase intention. Country of Origin has an significant and positive effect on purchase intention. Simultaneously religiosity, consumer ethnocentrism and country of origin has a significant influence on purchase intention with the constributions made (R^2) of 22,3% and the rest is explained by other variables.